Pengaruh Kualitas Pelayanan dan Fasilitas Terhadap Kepuasan Pelanggan di Toko Kamila Grosir Karawang - Soraya Widitasari; Puji Isyanto; Neni Sumarni (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The research was conducted with the aim of identifying the impact of service quality and facilities on the level of customer satisfaction at the Kamila Grosir Karawang store. The research method used was quantitative using a purposive sampling technique, and involved a sample size of 98 respondents who were customers who had visited or shopped at the shop. The analysis was carried out using multiple linear regression using the f test and t test, and a relevant level of 5%. The research results show that service quality is influenced and relevant to customer satisfaction, as well as facilities that have a relevant influence on customer satisfaction at the Kamila Grosir Karawang store. Apart from that, the quality of service and facilities simultaneously influences and is relevant to customer satisfaction at the Kamila Grosir Karawang store. It can be concluded from this research that the quality of service and facilities are mutually influenced by customer satisfaction at the Kamila Grosir Karawang store. There is an implication that maintaining consistency in service quality and providing services that meet customer needs can contribute to forming loyalty. Customers who feel valued and comfortable during the shopping process are more likely to remain loyal to the business.